Optical studies in distributed Bragg reflectors built from ZnO/MgO multilayer films - Huang, Y S; Chang, C C; Lee, J W; Lee, Y C; Huang, C C; Wun, Z K; Tiong, K K (Physica scripta, 2013)
We present the distributed Bragg reflectors (DBRs) with 10- and 15-period zinc oxide (ZnO)/MgO multilayer films deposited on silicon by sputtering technology. The reflectivity for the 10-period ZnO/MgO stacks can reach to 91.4% and for the 15-period ZnO/MgO stacks can be increased to 98.7%. Furthermore, the transfer matrix method takes account of the Sellmeier equation and the random thickness model, plus it can well describe the measured reflectivity spectra. The investigation indicates that a refined control of the individual layer thickness and the number of layer periods are significant subjects to improve the DBRs performance.